Phase stability, magnetic, electronic, half-metallic and mechanical properties of a new equiatomic quaternary Heusler compound ZrRhTiIn: A first-principles investigation. (May 2018) - Wang, Jia-Xing; Chen, Z.B.; Gao, Y.C.
Abstract: In this manuscript, we have studied the electronic, magnetic, half-metallic and mechanical properties of a new Zr-based equiatomic quaternary Heusler (EQH) compound, ZrRhTiIn using first-principles calculations. The generalized gradient approximation (GGA) calculation results imply that at its equilibrium lattice constant of 6.70 Å, ZrRhTiIn is a half-metallic material (HMM) with a considerable band gap (Ebg ) of 0.530 eV and a spin-filter/half-metallic band-gap (EHM ) of 0.080 eV in the minority-spin channel. For ZrRhTiIn, the formation energy of −2.738 eV and the cohesive energy of 21.38 eV indicate that it is a thermodynamically stable material according to theory. The minority-spin EHM arises from the hybridization among Zr-4d, Ti-3d and Rh-4d electrons. The calculated total magnetic moment of ZrRhTiIn is 2 μB, meeting the well-known Slater-Pauling rule Mt = Zt −18. Furthermore, uniform strain and tetragonal strain were applied in this work to examine the magneto-electronic and half-metallic behaviors of the ZrRhTiIn system. Finally, we show that ZrRhTiIn is mechanically stable, ductile and anisotropic. Highlights: ZrRhTiIn is a new HMM at its equilibrium lattice constant. ZrRhTiIn is mechanically stable, ductile and anisotropic. The total magnetic moment meets the Slater-Pauling rule.